ANALISIS IMPLEMENTASI KEBIJAKAN BADAN USAHA MILIKI DESA (BUMDes) DALAM PERENCANAAN PEMBANGUNAN DI KAMPUNG HOLTEKAMP DISTRIK MUARA TAMI KOTA JAYAPURA - Usman, Syamsudin (DINAMIS, 2023)
Village-owned enterprises (BUMDes) are entities established to enhance the village economy, increase local revenue, and optimize the management of village resources in line with community needs, thereby becoming the backbone of rural growth and economic equity. Their role is pivotal in promoting village autonomy and community welfare. BUMDes serves as an instrument for strengthening village autonomy and promoting community welfare. Its presence is crucial in empowering village governments and harnessing local potential within the village's capacity and authority. The policies formulated by BUMDes Kampung Holtekamp play a strategic role in village development planning. One of the policies crafted pertains to development planning within Kampung Holtekamp. This qualitative descriptive research employs data collection techniques such as interviews, observations, and literature reviews. Information sources include stakeholders and members of the Kampung Holtekamp community.